International M&A: Evidence on effects of foreign takeovers - Anselm Mattes (Institut für Angewandte Wirtschaftsforschung (IAW), 2010)
In this empirical paper I address the effects of international mergers and acquisitions (M&A) on the acquired firms. International direct investments in the home country are usually welcomed and considered to be beneficial for growth, employment, productivity and technological progress. This is mostly unquestioned for greenfeld investments, i.e. the case when a foreign multinational firm sets up a new affliate. But a majority of foreign direct investment (FDI) projects takes the form of mergers and acquisitions (M&A). This kind of inward FDI is much more critically debated. The focal point of this paper is the development of domestic German firms that are subject to a foreign takeover regarding employment and productivity. For this purpose, I use a comprehensive German microlevel dataset which includes all industries as well as firms from all size categories and all German regions. The sample covers the years from 2000 to 2007. A propensity score matching approach combined with a diferenceindiference estimator is applied. Contrary to a naive comparison between foreignowned firms and domestic firms or a comparison between firm characteristics before and after a foreign takeover, this econometric approach ensures that the causal effects are isolated. The main results are the following: Foreign owned firms are larger and more productive than domestic ones. Mostly firms with below average productivity (lemons) as well as firms with a relatively high productivity (cherries) are acquired. Market development motives seem to play an important role for foreign acquisitions. Concerning the effects of foreign takeovers, a descriptive analysis cannot find unambiguous effects of foreign takeovers. The propensity score matching estimator confrms this finding and detects neither positive nor negative significant effects of foreign takeovers.
Keywords: F23; J23; 330; M&A; inward FDI; foreign takeover; employment; productivtity; Übernahme; Direktinvestition; Ausländisch; Multinationales Unternehmen; Produktivität; Beschäftigungseffekt; Deutschland